2015
DOI: 10.1159/000381865
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Intravitreal Implant as Adjunctive Therapy to Ranibizumab in Neovascular Age-Related Macular Degeneration: A Multicenter Randomized Controlled Trial

Abstract: Purpose: To evaluate the efficacy and safety of dexamethasone intravitreal implant 0.7 mg (DEX) as adjunctive therapy to ranibizumab in neovascular age-related macular degeneration (nvAMD). Procedures: This was a 6-month, single-masked, multicenter study. Patients were randomized to DEX implant (n = 123) or sham procedure (n = 120) and received 2 protocol-mandated intravitreal ranibizumab injections. The main outcome measure was injection-free interval to first as-needed ranibizumab injection. Results: DEX inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…[20][21][22] Targeting angiogenesis and inflammation during disease progression seems to be reasonable, as inflammation has been shown to be involved in the pathogenesis of ME, and the possible benefit of a multimodal treatment approach including steroids has been recently investigated. 13,15 To date, limited evidence exists about the use of additional corticosteroid treatment in patients with nAMD. Hence, we evaluated the influence of anti-VEGF monotherapy or anti-VEGF and corticosteroid combined treatment on intraocular cytokine concentrations in persistent or recurrent nAMD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Targeting angiogenesis and inflammation during disease progression seems to be reasonable, as inflammation has been shown to be involved in the pathogenesis of ME, and the possible benefit of a multimodal treatment approach including steroids has been recently investigated. 13,15 To date, limited evidence exists about the use of additional corticosteroid treatment in patients with nAMD. Hence, we evaluated the influence of anti-VEGF monotherapy or anti-VEGF and corticosteroid combined treatment on intraocular cytokine concentrations in persistent or recurrent nAMD patients.…”
Section: Discussionmentioning
confidence: 99%
“…As inflammation is involved in the complex pathogenesis of nAMD, the role of intravitreal steroids, either as monotherapy or combined treatment, has been investigated to treat CNV lesions. 13,14 A multimodal treatment approach targeting angiogenesis and inflammation has recently been iovs.arvojournals.org j ISSN: 1552-5783 shown to reduce the amount of retreatments. 13,15 However, limited clinical evidence exists about the use of combined treatments in the management of nAMD patients.…”
mentioning
confidence: 99%
“…Compared with ranibizumab monotherapy, studies showed no long-term improvement of best corrected visual acuity (BCVA) and reduction of CMT; 22 25 however, DEX implant in some cases allowed a reduced number of anti-VEGF injections. 23 , 24 …”
Section: Namdmentioning
confidence: 99%
“…In a 6-month, singlemasked, multicenter study, the dexamethasone implant and ranibizumab (123 patients) provided the same efficacy and allowed a modest statistically significant reduction in the frequency of ranibizumab injections compared with ranibizumab used alone (120 patients). Increased IOP in this study (IOP ≥ 25 mm Hg) occurred in 18.2% of patients treated with the dexamethasone implant (Kuppermann et al, 2015) 67 . A sustained drug intravitreal delivery system with fluocinolone acetonide had the same goal in diabetic macular edema.…”
Section: Steroids and Other Immunomodulatorsmentioning
confidence: 55%